A bibliometric analysis of the global status of platelet-rich plasma in regenerative medicine from 2004 to 2023 - Siwen Zhang; Xudong Zhang; Haochen Zhang; Shengqing Zhang; Zichen Liu; Shanshan Wu; Yimeng Lu; Chao Han; Jichun Tan (Regenerative Therapy, 2025)
Introduction: Platelet-rich plasma (PRP) is a plasma product that concentrates platelets from whole blood and used widely in regenerative medicine. This study aimed to evaluate the evolution, development trend, and research highlights of research status of PRP in regenerative medicine. Methods: Publications related to PRP were retrieved from the Science Citation Index Expanded (SCIE) database of the Web of Science (WoS) in February 2024. The impact factor (IF) was used to evaluate and compare the contributions of different countries. Then, the top 10 countries, top 10 productive journals, top 10 WoS categories, and top 10 most cited articles were listed. The data was processed, and the relative contributions of the top 10 productive countries in each year were presented in a line chart and a heatmap. VOSviewer software and heatmap were used to investigate the holistic trend of research highlights according to the change trends of keywords. Results: A total of 9,577 publications were retrieved from SCIE database. The USA topped the list with 2,311 papers, followed by China (1,583 papers), the UK (525 papers), and Spain (512 papers). The studies of PRP in regenerative medicine have increasing trend globally. The USA had the most total citation and took the leading position for relative contributions, the UK ranked 1st in average citations and average IF. However, China's contribution had a dramatically increasing trend since 2015, and exceeded the USA in 2022. There were seven keywords of “Bone-related cluster”, “hyaluronic acid-related cluster”, “cartilage-related cluster”, “stomatology-related cluster”, “damage repair-related cluster”, “experiment-related cluster”, and “nerve-related cluster” generated in keyword co-occurrence analysis. Except for bone & joint diseases, novel clinical applications of PRP have been carried out, including dental and neurological practice, reproductive medicine, dermatology, gynecology, and plastic surgery, cosmetic treatments, and the improvement of non-musculoskeletal organ function. Conclusion: To summarize, the research advancements of PRP appear to be more prominent in the United States and China. Experimental research on PRP is mostly concentrated on exploring on mechanism and signal pathway. As an effective adjuvant treatment, the clinical application of PRP has expanded from initial trauma repair to multiple systemic organ disorders. Leveraging the intersection of multiple disciplines, the development of novel PRP-based medical materials tailored to specific disease characteristics may represent a promising direction for future research.